Investigation of mixed mode - I/II fracture problems - Part 1: computational and experimental analyses - O. Demir; S. Siriç; A. O. Ayhan; H. Lekesiz (Fracture and Structural Integrity)
In this study, to investigate and understand the nature of fracture behavior properly under in-plane mixed mode (Mode-I/II) loading, three-dimensional fracture analyses and experiments of compact tension shear (CTS) specimen are performed under different mixed mode loading conditions. Al 7075-T651 aluminum machined from rolled plates in the L-T rolling direction (crack plane is perpendicular to the rolling direction) is used in this study. Results from finite element analyses and fracture loads, crack deflection angles obtained from the experiments are presented. To simulate the real conditions in the experiments, contacts are defined between the contact surfaces of the loading devices, specimen and loading pins. Modeling, meshing and the solution of the problem involving the whole assembly, i.e., loading devices, pins and the specimen, with contact mechanics are performed using ANSYSTM. Then, CTS specimen is analyzed separately using a submodeling approach, in which three-dimensional enriched finite elements are used in FRAC3D solver to calculate the resulting stress intensity factors along the crack front. Having performed the detailed computational and experimental studies on the CTS specimen, a new specimen type together with its loading device is also proposed that has smaller dimensions compared to the regular CTS specimen. Experimental results for the new specimen are also presented.